Model Inovasi Pelayanan Pemerintah Daerah dalam Mitigasi Bencana - Herlina, Maria; Sipahutar, Hotnier; Wardani, Dyah Kusuma; Sulistyono, Djoko; Pribadi, Muhammad Akbar (Research and Development Agency Ministry of Home Affairs, 2021)
Indonesia has a geographical, geological, hydrological, and demographic situation prone to disasters with a relatively high frequency, thus requiring systematic, integrated, and coordinated disaster management. The disasters that occurred until 2020 were dominated by hydro-meteorological natural disasters such as floods, landslides, hurricanes, droughts to forests, and land fires (BNPB, 2021). The purpose of this study is to identify innovation models for regional government services in disaster mitigation. This study uses a qualitative descriptive method with data collection techniques, namely literature studies, FGDs, and interviews with related disaster mitigation innovations at the research location. The field findings illustrate that the SDIS innovation implemented by Sleman Regency is among the best innovations in handling volcanic eruptions. This innovation has been initiated since 2016 and continues to be refined. In the city of Semarang, specifically for flood disasters, the Early Warning System tool was installed at several points as the best innovation in flood management. However, difficulties were installing it at certain points due to geographical contours that were impossible. Meanwhile, for Sumedang Regency, their innovation through the SITABAH application still needs further development to become the best innovation in landslide mitigation due to limitations in infrastructure and human resources. In addition, the application is still one-way. Of the three disaster mitigation innovation models, the SDIS innovation is an innovation that has been successfully implemented by the Regional Disaster Management Agency of Sleman Regency. Especially on the